Influence of long-term caloric restriction on myocardial and cardiomyocyte contractile function and autophagy in mice - Han, Xuefeng; Turdi, Subat; Hu, Nan; Guo, Rui; Zhang, Yingmei; Ren, Jun (The Journal of nutritional biochemistry, 2012)
Both clinical and experimental evidence has revealed that calorie restriction (CR) is capable of improving heart function. However, most the reports are focused on the effect of CR on the pathological states such as obesity, while the effect of CR on heart function in otherwise healthy subjects is not well understood. This study examined the long-term CR effect on cardiac contractile function and possible underlying mechanisms involved. C57BL/6 mice were subjected to a 40% CR or ad libitum feeding for 20 weeks. Echocardiographic and cardiomyocyte contractile properties were evaluated. Intracellular signaling pathways were examined using Western blot analysis. Our results showed that CR overtly lessened glucose intolerance, lessened body and heart weights (although not heart size), lowered fat tissue density, decreased left ventricular (LV) wall thickness (septum and posterior wall) in both systole and diastole, and reduced LV mass (not normalized LV mass) without affecting fractional shortening. Cardiomyocyte cell length and cross-sectional area were reduced, while peak shortening amplitude was increased following CR. CR failed to affect maximal velocity of shortening/relengthening and duration of shortening and relengthening. Immunoblotting data depicted decreased and increased phosphorylation of Akt/glycogen synthase kinase-3β and AMP-dependent protein kinase/acetyl-CoA carboxylase, respectively, following CR. CR also dampened the phosphorylation of mammalian target of rapamycin, extracellular-signal-regulated protein kinase 1/2 and c-Jun, while it increased the phosphorylation of c-Jun NH2-terminal kinase. Last but not least, CR significantly promoted cardiac autophagy as evidenced by increased expression of LC3B-II (and LC3B-II to LC3B-I ratio) and Beclin-1. In summary, our data suggested that long-term CR may preserve cardiac contractile function with improved cardiomyocyte function, lessen cardiac remodeling and promote autophagy.